Mental Healty dan Literasi Keuangan Wanita: Antara Karier dan Ibu Rumah Tangga - Wasti Reviandani (Jurnal Pengabdian Manajemen, 2023)
Today more and more women are having careers outside the home, especially those working in offices, in certain places and this always raises pros and cons. Women work, wives work, this sometimes creates problems in the family. Some cannot accept it, some accept it, some do it with an open heart, some do it with a guilty heart. There are women who work but are constantly plagued with guilt because they think they should be at home. The purpose of the service is to explain in more detail solutions to solving problems regarding the positive and negative sides of women's dual roles and regarding the mechanisms for managing or managing time. The socialization was carried out face-to-face with Almadany Elementary School teachers. Along with presenting the material, the implementing team showed a video that had been made by the implementing team on Youtube regarding women's mental health. The final result is that participants can understand how to maintain mental health in multiple roles.